KUAT TEKAN BETON DENGAN PENAMBAHAN SERBUK KAYU - Randy C Manuel,; Jeffrey A. Delarue,; Titof Tulaka, (Sustainable Construction (SUSCON), 2024)
Better concrete quality is required as concrete technology advances, both in terms of the type of concrete mixture used and the amount of additional ingredients added to the mixture to boost the strength of the concrete. The waste product of the sawmill business is called sawdust. Adding it to the concrete mixture when adding fine aggregate is one way to go about it. This research attempts to ascertain the compressive strength of sawdust-added concrete as well as the outcomes of contrasting regular concrete with sawdust additions to fine aggregate at percentages of 3%, 5%, and 7%. SNI 03-7656-2012 was the planning combination utilized in this investigation. It included a plan for compressive strength of 16 MPa and concrete tests at 7, 14, and 28 days of age. According to the test results, the percentages of 3%, 5%, and 7% had average compressive strength values of 18,50 MPa, 10,36 MPa, and 7.77 MPa at 28 days of age. The intended value of 16 MPa for compressive strength is exceeded by typical concrete after 28 days, reaching a value of 19,79 MPa. Based on the study's findings, it can be said that the concrete's compressive strength decreases with increasing proportion of cempaka sawdust used in place of fine